PENGEMBANGAN BAHAN AJAR IPAS BERBASIS MULTIKULTURAL SUKU SASAK DALAM MATERI INDONESIAKU KAYA BUDAYA KELAS IV SDN 2 AMPENAN - Hidayati, Putri; Sobri, Muhammad; Widhi Andika, I Putu Herry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop multicultural teaching materials based on the Sasak Tribe in the content of Science Chapter 6 of grade IV SDN2 Ampenan. The type of research used is Research and Development (R&D) with the development model of Analysis, Design. Development, Implementation, Evaluation (ADDIE). Data collection in this study used questionnaires and documentation. Questionnaires were given for validation by material experts, validation by media experts, and student responses. While documentation was obtained from pictures or photos in research activities. Data analysis was carried out qualitatively and quantitatively, using a scoring table and a percentage of feasibility. The results showed that the teaching materials developed obtained a media expert validation score of 93% with a very valid category, and a material expert validation score of 83% with a very valid category. The practicality test showed a positive response from students of 92% with a very practical category and a teacher response of 98% with a very practical category. This shows that the Sasak tribe multicultural learning module is suitable for use in learning Science Chapter 6 of grade IV. This teaching material can help students understand the material more easily because it is directly related to their culture and environment, and supports the goals of the Independent Curriculum which emphasizes contextual learning.